Surface roughness effects on electromechanical performance of RF-MEMS capacitive switches. (January 2020) - Nawaz, Hamid; Masood, Muhammad Umar; Saleem, Muhammad Mubasher; Iqbal, Javaid; Zubair, Muhammad
Abstract: The effect of surface roughness on the electromechanical performance of radio frequency micro-electromechanical system (RF-MEMS) based capacitive switches is an important reliability concern. This paper presents a finite element method (FEM) based simulation methodology for the estimation of surface roughness effects on the electromechanical characteristics of parallel plate capacitive RF-MEMS switch. The important electromechanical characteristics considered for the analysis of surface roughness effect include up-state capacitance, down-state capacitance, pull-in voltage, pull-in gap and switching time of RF-MEMS switch. A simple roughness model is employed consisting of semi-circles of constant radius along the surface of an RF-MEMS switch. It is shown that there are significant, but predictable shifts in electromechanical characteristics of RF-MEMS switch due to surface roughness. The results illustrate that the normalized value of up-state capacitance and pull-in gap increases, whereas the values of downstate capacitance, pull-in voltage and switching time decreases with an increase in surface roughness. The change in pull in voltage for an initial air gap of 0.4 μm and roughness of 50 nm is around 28.5% which is about quarter the value of voltage required for the actuation of smooth surface RF-MEMS switch. The results obtained through FEM based analysis in this work are in good agreement with the adopted analytical model and experimental results presented in literature. Highlights: The presence of surface roughness affects both the electromechanical and RF characteristics of RF-MEMS Switches. The effect of surface roughness on capacitance, pull-in voltage, pull-in gap and switching time of an RF MEMS capacitive switch has been studied. The roughness effect on the electromechanical characteristics increases with decrease in air gap present between suspended bridge and bottom dielectric layer. The roughness effect increases when the gap is of order of the roughness scale. The capacitance and pull-in gap increase with an increase in roughness The pull-in voltage and switching time decrease with an increase in the roughness